Model for estimating the water supply incorporating groundwater in micro-basins without hydrologic informati (2017)
(Eng) Surface water (SUP) and groundwater (SUB) interact inside the hydrological cycle according to geomorphologic and climatic characteristics that compose the landscape. Therefore, the impact on any of these compounds will inevitably affect the quantity and/or quality of the other. In this context, a simple method was proposed based on the general water balance equation; which incorporates the exchange flow of superficial and groundwater in the estimate of the total water availability (OHtotal) in a watershed, starting from minimum hydroclimologic and hydrogeologic data. This method was applied to the micro-basin of La Arenosa-La Margarita creek (Pereira, Colombia) and it was noticed that the input of the groundwater flow influences in the estimate of the water availability. Also, it was analyzed that these results are quite similar to the ones obtained by widely used theoretical models used in hydrology; such as the SCS, UNESCO, added tanks, Long-term hydric balance and Hydric Efficiency for the same study area. Thus, it was concluded that the proposed method is viable to be applied in micro-basins with little hydrologic and hydrogeological information.